Dialog na styku kultur — Bieszczady - Węcławiak, Alicja (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Eastern Slavonic cultures are often a conglomeration of patterns of several cultures, which resulted from the past. As Paul Ricouer said, the past is a place of our hidden identity, hurt by the greatest disaster of the twentieth century — bloody regimes. Nazism and bolshevism left their mark on the western world, whose painful consequences we still face today. Bieszczady is a part of Poland, which suffered particularly acutely during and after WWII. It is a place with a kind of a legend, becoming more and more appreciated, because of its tourist attractions, unspoiled nature, magical and largely virginal landscapes. This is a very important area for Slavonic identity, a place with a rich and troubled history — Bieszczady witnesses the actions of the Ukrainian InsurgentArmy and Operation “Vistula”. This article concerns this question, presents excerptsof interviews and memories of participants in those events and shows Bieszczady as a region of the heterogeneous Slavonic culture and a place of memory — both individual and collective.